2021
DOI: 10.1021/acs.cgd.1c00042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Solid-State Structural Chemistry of Uranium(IV) Aliphatic Dicarboxylates

Abstract: Examinations of uranium­(IV) complexation by aliphatic dicarboxylates, ranging from the three-carbon malonate to the six-carbon adipate, yielded six novel phases. Single crystals of the compounds were prepared through either evaporation or solvent layering, and the structures were determined via single-crystal X-ray diffraction. The compounds were further characterized via IR and Raman spectroscopies. For the phases synthesized via solvent layering, correlations between the solution- and solid-state speciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The differences between ν as (COO – ) and ν s (COO – ) stretches (Δ) of 199 and 110 cm –1 for 1 , 224 and 90 cm –1 for 2 , and 200 and 96 cm –1 for 3 which are the characteristic features of monodentate terminal and μ:η 1 :η 1 - syn - syn bidentate coordination of carboxylate groups, respectively, are in agreement with previous studies. The band detected at higher stretching frequencies of 1605, 1609, and 1608 cm –1 for 1 , 2 , and 3 respectively, which can be attributed to ν­(CN) vibration of the pyridine moiety of the ligand backbone, is most probably overlapped with one of the asymmetric modes of benzoate groups. Furthermore, the characteristic stretching frequencies of 3420, 3416, and 3397 cm –1 for 1 , 2 , and 3 , respectively, are indicative of the noncoordinating hydroxyl ν­(O–H) groups of lattice waters/moisture …”
Section: Resultsmentioning
confidence: 99%
“…The differences between ν as (COO – ) and ν s (COO – ) stretches (Δ) of 199 and 110 cm –1 for 1 , 224 and 90 cm –1 for 2 , and 200 and 96 cm –1 for 3 which are the characteristic features of monodentate terminal and μ:η 1 :η 1 - syn - syn bidentate coordination of carboxylate groups, respectively, are in agreement with previous studies. The band detected at higher stretching frequencies of 1605, 1609, and 1608 cm –1 for 1 , 2 , and 3 respectively, which can be attributed to ν­(CN) vibration of the pyridine moiety of the ligand backbone, is most probably overlapped with one of the asymmetric modes of benzoate groups. Furthermore, the characteristic stretching frequencies of 3420, 3416, and 3397 cm –1 for 1 , 2 , and 3 , respectively, are indicative of the noncoordinating hydroxyl ν­(O–H) groups of lattice waters/moisture …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the synthesis of new polymeric networks of U­(IV) is considerably less developed with most previously reported U­(IV) polymer based either on oxalate or phosphonate ligands. In particular, the use of aromatic polycarboxylic linkers remains rare in U­(IV) chemistry despite the fact that has proven a convenient strategy for the synthesis of stable three-dimensional (3D) frameworks with different topologies and permanent porosity. ,, Monotopic aromatic carboxylates (benzoate), reported by us and others, lead to the controlled assembly of molecular oxo clusters of diverse nuclearity {U 6 } {U 10 },{U 12 },{U 13 }­{U 16 } and {U 24 }, depending on the reaction stoichiometry, solvent, and temperature. Using a different approach, Loiseau and Falaise showed that the use of ditopic aromatic carboxylates in solvothermal conditions leads to the formation of 3D networks based on the hexanuclear uranium-centered motif [U 6 O 4 (OH) 4 (H 2 O) 6 ] . Very recently, Long et al reported a similar permanently porous uranium­(IV) framework based on a ditopic aromatic carboxylate that showed self-adjusting binding pockets that enhance CH 4 and H 2 absorption .…”
Section: Introductionmentioning
confidence: 99%